#junkfluenced: the marketing of unhealthy food and beverages by social media influencers popular with Canadian children on YouTube, Instagram and TikTok - Monique Potvin Kent; Mariangela Bagnato; Ashley Amson; Lauren Remedios; Meghan Pritchard; Soulene Sabir; Grace Gillis; Elise Pauzé; Lana Vanderlee; Christine White; David Hammond (BMC, 2024)
Abstract Background Marketing of unhealthy foods to children on digital media significantly impacts their dietary preferences and contributes to diet-related noncommunicable diseases. Canadian children spend a significant amount of time on digital devices and are frequently exposed to unhealthy food marketing on social media, including by influencers with celebrity status who endorse products. This study aimed to examine the frequency, healthfulness, and power of unhealthy food marketing in posts by influencers popular with Canadian children on YouTube, Instagram and TikTok. Methods The top 9 influencers popular amongst Canadian children aged 10-12 years were identified from the 2021 International Food Policy Study Youth Survey. A total of 2,232 Instagram, YouTube and TikTok posts made by these influencers between June 1st 2021 and May 31st 2022 were examined for instances of food marketing. Food products/brands were identified and frequencies were calculated for the number of posts promoting food products/brands, posts promoting products/brands classified as less healthy according to Health Canada's Nutrient Profile Model (2018) and marketing techniques utilized. Results YouTube had the highest average rate of food marketing instances per post, at a rate of 1 food marketing instance every 0.7 posts, while TikTok and Instagram had instances every 10.2 posts and 19.3 posts, respectively. Overall, fast food restaurants was the most promoted food category (21%), followed by regular soft drinks (13%), snacks (11%), candy and chocolate (11%) and water (8%). The most frequently used marketing techniques were appeals to fun/cool (37%), the use of songs or music (28%) and the product being consumed (25%). In terms of healthfulness, 83% of the products/brands (87% of brands and 82% of products) promoted were classified as less healthy. Conclusions Social media influencers play a substantial role in promoting unhealthy food products to children, primarily fast food items. Given the significant impact of such marketing on children, there is a need for ongoing government-led monitoring, and it is crucial to include social media and influencer marketing in marketing restrictions targeting children in Canada to safeguard this vulnerable demographic.